Case Report: Dislocation of lateral menisci secondary to congenital lateral tibiofemoral cartilage thickening in both knees - Zhang, Xingliang; Li, Wentao; Li, Zijin; Xie, Yibing; Zhu, Chenyu; Lei, Shaoyang; Zhang, Shuqian (Frontiers in Surgery, 2024)
A 24-year-old male complained of mild knee pain after jogging. The subsequent bilateral knee MRI demonstrated. bilateral lateral thickened tibiofemoral cartilages thickening were evidenced by the deformity of bilateral subchondral bone beneath the lateral femoral condyle cartilage. The corresponding dislocation of almost the total all the left lateral meniscus and part of the right lateral meniscus to the center of the joint were detected. After excluding the diagnosis of congenital RSM, BHT of C-shaped lateral meniscus and central tear of discoid meniscus, the displacement of all or part lateral meniscus to the intercondylar notch was considered as a consequence of the congenital thickening of lateral superior and inferior cartilage. This case might report a new variant in knee joint so far.